Creation of Safe Space in COVID-19 Pandemic – A Case Study of Republic of Croatia - Cesarec, Ivana (JASSP, 2022)
COVID-19 changed our cotemporary world, the way we work and the way we travel. The latter is a major challenge for countries that are heavily dependent on tourism, and Croatia is one of those countries with the largest tourism share of the total gross domestic product (GDP) in Europe - 25% in pre-pandemic times (2019 data). In the last two years, travel for tourism has decreased - both due to restrictions and due to people’s fear of coronavirus infection. Therefore, under the influence of the health crisis posed by pandemic, there is an increasingly relevant sense of health safety that can be considered as a prerequisite for the success of tourism destination. This paper aims to research and analyze the concept of “safe space” and its creation in pandemic conditions where the application of health and security protocols is expected, and on the example of the Republic of Croatia to evaluate the efforts and possible effect of undertaken measures. The research design is based on quantitative-qualitative desktop analysis of pandemic-related processes and key data which evaluate the impact of the COVID-19 pandemic on the tourism sector from several stakeholders’ perspectives - consumer and service provider. The result of this research shows that the perception of a safe space has a positive impact on the tourist interest in the COVID-19 pandemic, which confirms the need for the tourism sector to adapt to the new security risks posed by the pandemic.